A study on the price discount threshold (PDT) and price premium threshold (PPT) of Singaporean consumers. - Ling, Tai Khiang. (2008)
In Singapore, it is not uncommon to find stores advertising 50, 60 or even 70% discounts. The question now is how much discount is enough for consumers to perceive a difference and how much discount is needed such that retailers do not lose out too much. With sales and discounts prevalent everywhere these days, one worry is that when consumers are constantly given % discounts, the impact of these discounts may have diminished as they have been conditioned to it.